2021
DOI: 10.3390/antiox10101579
|View full text |Cite
|
Sign up to set email alerts
|

Development of an Optimized Drying Process for the Recovery of Bioactive Compounds from the Autumn Fruits of Berberis vulgaris L. and Crataegus monogyna Jacq.

Abstract: Hot air drying has proven to be an efficient method to preserve specific edible plant materials with medicinal properties. This is a process involving chemical, physical, and biological changes in plant matrices. Understanding these processes will lead to an improvement in the yields of bioactive compounds. This study aims to optimize the drying process of two species’ fruits used in folk medicine, Berberis vulgaris and Crataegus monogyna. The optimized extracts’ antioxidant capacity was assessed using various… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 57 publications
0
7
0
1
Order By: Relevance
“…Methods that are conventionally used for optimisation purposes, where the influence of one factor is studied at a time, present a major shortcoming. They do not consider potential interactions between factors, which can mislead in identifying the optimal combination of critical process parameters [21] , [22] , [23] . The recently alternative of using the Design of Experiments (DoE) to find optimal product and process characteristics provides the highest amount of information from the least number of experimental runs by systematic variation of the factors and simultaneously evaluation of the effects of multiple variables.…”
Section: Introductionmentioning
confidence: 99%
“…Methods that are conventionally used for optimisation purposes, where the influence of one factor is studied at a time, present a major shortcoming. They do not consider potential interactions between factors, which can mislead in identifying the optimal combination of critical process parameters [21] , [22] , [23] . The recently alternative of using the Design of Experiments (DoE) to find optimal product and process characteristics provides the highest amount of information from the least number of experimental runs by systematic variation of the factors and simultaneously evaluation of the effects of multiple variables.…”
Section: Introductionmentioning
confidence: 99%
“…The Q-DPPH method showed 874 mg Trolox equivalent (TE) per 100 g (dw). This value is lower than Moldovan et al, (2021) reported (3434 mg TE/100 g of dw) because, in their study, the antioxidant activity was determined in the extract of the whole fruit [ 30 ]. Respecting the Q-FRAP method, an average result of 13.781 mg Trolox equivalent per 100 g of dry weight was obtained; this value was higher than Moldovan et al, (2021) reported (7434 mg TE/100 g dw), despite using fruit extracts [ 30 ].…”
Section: Resultsmentioning
confidence: 84%
“…In a study conducted to examine the effect of B. vulgaris fruit in patients with primary biliary cholangitis who did not respond to treatment, the total phenolic content of B. vulgaris extract was calculated to be 105 ± 12 mg/mL [ 26 ]. In another study, B. vulgaris extract was evaluated in terms of total phenolic content and the obtained value was 100.862 ± 1.967 mg/mL [ 27 ]. Research conducted in the Sivas province of Turkey noted the total phenolic component content of fresh fruits that were collected and immediately processed ranged from 256.5 to 362.9 mg/mL [ 28 ].…”
Section: Discussionmentioning
confidence: 99%